Development of The Principle of Beneficial Ownership Identification of a Corporation and Their Implications for Tax Paying Obligation - Rizky Imanuel Tampubolon; Umi Khaerah Pati (Journal of Law, Society, and Islamic Civilization, 2024)
Business has a significant role in the Indonesian economy, contributing through tax revenue and foreign exchange. Nevertheless, violations such as manipulation and tax evasion by some companies can adversely affect economic growth. One strategy for tax avoidance is through Beneficial Ownership, especially with the treaty shopping scheme, which can result in significant losses in national tax revenue. The focus of this research is on the implementation of the "recognizing beneficial ownership" principle and increasing data transparency as a preventive measure against tax avoidance strategies. The aim of this study is to examine the implications of applying the principle of recognizing the beneficial ownership of corporations on tax payment obligations. This research uses a normative legal research method with a statutory approach. The implementation of rules related to beneficial ownership in Indonesia, especially after the enactment of Presidential Regulation No. 13 of 2018, is considered a key step in addressing tax avoidance. However, this study indicates that despite the regulations being in place, further preventive efforts are needed, such as the application of Limitation on Benefits and Principal Purpose Test, to prevent treaty shopping and ensure that transactions or agreements are not solely aimed at obtaining tax benefits.